If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(9h + -1) = h + 6 Reorder the terms: 5(-1 + 9h) = h + 6 (-1 * 5 + 9h * 5) = h + 6 (-5 + 45h) = h + 6 Reorder the terms: -5 + 45h = 6 + h Solving -5 + 45h = 6 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. -5 + 45h + -1h = 6 + h + -1h Combine like terms: 45h + -1h = 44h -5 + 44h = 6 + h + -1h Combine like terms: h + -1h = 0 -5 + 44h = 6 + 0 -5 + 44h = 6 Add '5' to each side of the equation. -5 + 5 + 44h = 6 + 5 Combine like terms: -5 + 5 = 0 0 + 44h = 6 + 5 44h = 6 + 5 Combine like terms: 6 + 5 = 11 44h = 11 Divide each side by '44'. h = 0.25 Simplifying h = 0.25
| A=32x-x^2 | | -6x+40=-8-6(7x-8) | | 6.5v=9.75 | | 600=3x*y | | 10=10+v/1 | | 10/11=b/22 | | 60=3x*y | | 0=35x-0.7x^2 | | 6.5xz=39 | | 54/a=9/10 | | 1/4.x=12 | | 3/8=b/32 | | 2x+3=16(2x-3) | | 5-8n=61 | | 9/7=63/× | | 3/4x# | | x/.5=.13/1 | | 8=v/3+3 | | 3(9a+4b)-8(a+2b)= | | 218.75=35x-0.7x^2 | | N/49=2/7 | | -44=5x+6 | | 685=x+3(.15*x) | | 3p+12=-6(2p-7) | | -1.4x+35=0 | | 685=x+3(.2*x) | | 2x+32=3+8x-7 | | 36=-3a-3 | | y+71=2x | | 6-8x-2=-46+4x-10 | | -4x^3-12x^2+x+3=0 | | 4+9x=103 |